Perspektif Ibnu Khaldun Tentang Pendidikan Agama Islam - Windu Gumati, Redmon (TADRUSUUN: JURNAL PENDIDIKAN DASAR, 2022)
Ibn Khaldun is one of the prominent Islamic thinkers who has a great influence on the development of science. Ibn Khaldun is more widely known as a historian and socialist. While his expertise in the field of education has received less attention, even if there is he has not provided an in-depth analysis. In fact, as stated in his work Muqoddimah Ibn Khaldun, apart from having a useful concept of education to be developed, he also acts as an educator. The concept of Ibn Khaldun's thought from an educational perspective is the result of Ibn Khaldun's thinking which emphasizes education. Ibn Khaldun's view of education is based on philosophical-empirical concepts and approaches. Through this approach, he provides direction towards the ideal and practical vision of the goals of Islamic education. The research method used in writing this Research is the critical historical method. The first step is heuristics, namely the activity of collecting traces of the past or the stage of gathering sources. The second stage is verification, which is an activity to examine historical sources both externally and internally. After doing the verification, then do the interpretation. Interpretation or interpretation consists of analysis and synthesis. Analysis means to unravel, and synthesis means to put together. The four historiographies, or historical writing, combine from each of the stages above to be presented in historical work. Based on the results of research from the literature that has been done that Ibn Khaldun is a great figure in the Islamic world, who managed to make such a big contribution in the world of science in the world. The thoughts of Ibn Khaldun actually cannot be separated from the roots of Islamic thought. Ibn Khaldun considers that education is the essence of human existence. Ibn Khaldun argues that education seeks to give birth to a cultured society and seeks to preserve the existence of society in the future. Ibn Khaldun's view of education is based on philosophical-empirical concepts and approaches. Through this approach, he provides direction towards the ideal and practical vision of the goals of Islamic education. The challenge of education according to Ibn Khaldun is that education can realize quality human resources, namely giving birth to a cultured society and trying to preserve and improve for the existence of the next community.